Stimulating low-carbon vehicle technologies: Summary and coclusions - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
If the transport sector is to make deep cuts to its carbon emissions, it is necessary to reduce the carbon-intensity of travel. Reducing travel itself, at some times and places, is sometimes justified but it is extremely unlikely that under expected global economic development patterns overall demand will decline. This holds true even if there is saturation in some markets and demand management policies are widely adopted. Technological change is therefore crucial. The emerging view is that the focus for decarbonising transport should be first to improve the fuel efficiency of conventional engines and then gradually introduce alternative technologies.
Keywords: 330